2008
DOI: 10.17221/358-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary selenium on lipid oxidation, selenium and vitamin E content in the meat of broiler chickens

Abstract: An experiment was conducted to compare the effect of dietary sodium selenite and selenomethionine on selenium and α-tocopherol concentration in breast meat, oxidative stability of meat in broilers, and on growth performance, but only as an unimportant criterion in this case. Sexed broiler cockerels Ross 308 were allocated to 3 dietary treatments, each comprising 100 chickens. The basal diet was supplemented with 0 (control) or 0.3 mg/kg Se from sodium selenite (SS) or selenomethionine (SM). Dietary supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 21 publications
10
28
0
Order By: Relevance
“…GSH) were increased, while the metabolic product of lipid peroxides of MDA content was decreased. The outcome was in agreement with the results of Skřivan et al (2008Skřivan et al ( , 2010. These findings suggested that Se improved the antioxidant property of broilers by elevating activities of antioxidant enzymes and concentrations of antioxidant and reducing peroxidation products, and also implicated that Se-Met supplementation may have a more beneficial effect on oxidative stability than SS.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…GSH) were increased, while the metabolic product of lipid peroxides of MDA content was decreased. The outcome was in agreement with the results of Skřivan et al (2008Skřivan et al ( , 2010. These findings suggested that Se improved the antioxidant property of broilers by elevating activities of antioxidant enzymes and concentrations of antioxidant and reducing peroxidation products, and also implicated that Se-Met supplementation may have a more beneficial effect on oxidative stability than SS.…”
Section: Discussionsupporting
confidence: 88%
“…results are presented as means ± SD, n = 3 SS = sodium selenite; Se-Met = selenomethionine; Hunter a value = redness a,b,c means within rows with different superscript letters differ significantly (P < 0.05) tion, which was in good agreement with findings of Moksnes and Norheim (1986) and Skřivan et al (2008Skřivan et al ( , 2010. It is known that organic Se has a higher bioavailability than inorganic Se for the Se deposition in the tissues (Mahan and Parrett, 1996).…”
Section: Discussionsupporting
confidence: 85%
“…Accordingly, Dlouhá et al (2008) or Skřivan et al (2008a) confirmed that organic sources of selenium increased its content in breast meat. The organic form of selenium is deposited to a greater extent than the inorganic form.…”
mentioning
confidence: 70%
“…Skřivan et al (2008a) found out the positive effect of organic and inorganic selenium form on an increase in body weight and Ševčíková et al (2006) or Dlouhá et al (2008) also reported the positive effect of organic selenium source. But other authors (Choct et al, 2004;Yoon et al, 2007) did not observe any significant differences in the final body weight of chickens after addition of selenium in organic form.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation